Desenvolvimento de um WebLab para estudo de efeitos não-lineares em fibras ópticas - Pessôa Filho, Joaquim (2016)
The advent f the Internet and the development of Information and Communication Technologies generated new spaces for communication and collaboration between groups of people in geographically distinct regions. The association of Web Technology with instrument automation and control by computer has made possible the development of the so called Remote Laboratories or WebLabs distributed environments that allow to access and control experiments remotely through a network or the Internet in real time and with the sensation of presence. In this work, a WebLab was developed for the study of non-linear effects in optical fibers, aiming to support and complement activities in face-to-face and distance courses on Optical Communications. Applications and graphic user interfaces were developed for instrument control and data acquisition in a remote experiment for measuring the non-linear coefficient of an optical fiber using the Continuous Wave Self-Phase Modulation Method. An application integrated to the user interface was also developed for the numerical simulation of the measurement through the integration of the Non-linear Schrödinger Equation by the Split-Step Fourier Method as well as a component based on Java Media Framework for audio and video transmission during the remote execution of the experiment. This work is part of the activities related to the participation of the Mackenzie Photonics Laboratory in the KyaTera Project of FAPESP´s TIDIA Program.